Principal’s Administrative Behaviour with Reference to Teachers’ Attitude Towards Teaching - Rizvi, Nusrat A. (INDIAN EDUCATIONAL REVIEW, 2014)
The most crucial factor of an educational institution is the administrative behaviour of its Principal which reflects the efficiency of the school functioning and besides this, it is the Principal who shapes the learning climate of the institution by developing a positive attitude among the teachers towards teaching. Thus the Principal’s behaviour influences teachers as well as students of his/her institution.Present study attempts to ascertain the administrative behaviour of the secondary school Principals and attitude of the teachers towards teaching. Besides ascertaining the different levels of the administrative behaviour of secondary school Principal, the study also attempts to compare the Principal’s differential administrative behaviours in respect of their teachers’ attitude towards teaching. The study was confined to 60 Higher Secondary and Intermediate Colleges of Meerut region. For achieving the objectives of the present study two methods of research i.e., Normative Survey and Causal Comparative Methods were used. For calculation and interpretation of data the investigator used two standardised tools. For measuring various dimensions of the Principal’s administrative behaviour PBDQ (Principal’s Behaviour Description Questionnaire) and for measuring teachers’ attitude towards teaching TAI (Teachers’ Attitude Inventory) were used. For calculation and interpretation of data statistical analysis (i.e. ‘F’ test and’t’ test) was used. The findings of the study indicate that the secondary school Principal who differ on their administrative behavioural characteristics such as Extrocentric nature, Interactive nature, Democratic nature, Progressiveness, Flexibility, Achievement Oriented quality and Tolerance also differ significantly with reference to their teachers’ attitude towards teaching.